Correct Question:-
Solve the following differential equation using Laplace transformation.
![\rm{x''(t)+x'(t)=2,\quad x(0)=3,\quad x'(0)=1}](https://img.qammunity.org/2023/formulas/mathematics/high-school/rjq9sk7gyhcbtbf3gewk0sy129me8e0oo4.png)
where
![\rm{x'(t)=(dx)/(dt),\quad x''(t)=(d^2x)/(dt^2).}](https://img.qammunity.org/2023/formulas/mathematics/high-school/8zwflg1a03ysqwnbv0h7ezrhdgecawom8s.png)
![\quad](https://img.qammunity.org/2023/formulas/mathematics/high-school/sf8j0uw8zeq6itu8q0bnbfp6w2kiibev6a.png)
Solution:-
Let,
![\cal{L}\{\rm{x(t)}\}=X(s)](https://img.qammunity.org/2023/formulas/mathematics/high-school/pdpappfeyjatbtp11cn8lu8uygl97zz8wg.png)
![\cal{L}^{\rm{-1}}\{\rm{X(s)}\}=x(t)](https://img.qammunity.org/2023/formulas/mathematics/high-school/ti5y8qo28hv2332u2j69s7a19pyyormsvg.png)
Given,
![\longrightarrow\rm{x''(t)+x'(t)=2}](https://img.qammunity.org/2023/formulas/mathematics/high-school/pqez1shtbl2kmzmyfgj9qsfzo1xcdl9y1p.png)
We take Laplace transformation of both sides of the equation.
![\longrightarrow\cal{L}\{\rm{x''(t)+x'(t)}\}=\cal{L}\{\rm{2}\}](https://img.qammunity.org/2023/formulas/mathematics/high-school/q1bi8g1flbwi79k3i45rg02norgij78r4n.png)
![\longrightarrow\cal{L}\{\rm{x''(t)}\}+\cal{L}\{\rm{x'(t)}\}=\cal{L}\{\rm{2}\}](https://img.qammunity.org/2023/formulas/mathematics/high-school/cwbuk68nxisfcrqxmwcpy6gd8orm7z0wan.png)
We have,
![\cal{L}\{\rm{x''(t)}\}=\rm{s^2\,X(s)-s\,x(0)-x'(0)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/g9n3xfnmpz6iazw3x9ff05om34do2qnc6p.png)
![\cal{L}\{\rm{x'(t)}\}=\rm{s\,X(s)-\,x(0)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/2997xtjl3f0kw4rjl4mjxdxrycabfki7td.png)
![\cal{L}\{\rm{2}\}=\rm{(2)/(s)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/6zgn5crws41s8aqhlrwe24novtvtlfzycg.png)
Then,
![\small\text{$\longrightarrow\rm{\big[s^2\,X(s)-s\,x(0)-x'(0)\big]+\big[s\,X(s)-x(0)\big]=(2)/(s)}$}](https://img.qammunity.org/2023/formulas/mathematics/high-school/t1jmlgy22wcuanqgdmewwkoism31v3rulc.png)
![\longrightarrow\rm{s(s+1)\,X(s)-(s+1)\,x(0)-x'(0)=(2)/(s)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/65juwz554gvb5w2f9bp4mr8cictk2y5hny.png)
Given that
and
Then,
![\longrightarrow\rm{s(s+1)\,X(s)-3(s+1)-1=(2)/(s)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/8q1gccazpvbfqt9cqqw69em0n4jl9yxe2g.png)
![\longrightarrow\rm{s(s+1)\,X(s)-3s-4=(2)/(s)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/49fjrl2sz765vr9kf2ayhu124mrxfck4oq.png)
![\longrightarrow\rm{s(s+1)\,X(s)=(2)/(s)+3s+4}](https://img.qammunity.org/2023/formulas/mathematics/high-school/hhlygyf4yncmprv3hovthvn5niv9c254w5.png)
![\longrightarrow\rm{X(s)=(2)/(s^2(s+1))+(3s+4)/(s(s+1))}](https://img.qammunity.org/2023/formulas/mathematics/high-school/zsyhfc5qlqkheo3lggt5f5gvh8apoda7me.png)
![\longrightarrow\rm{X(s)=(3s^2+4s+2)/(s^2(s+1))\quad\dots(1)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/iv6b4wo1ost1fignmuxx8fkgoddfbyooz7.png)
We will factorise this expression by partial fractions.
Assume,
![\longrightarrow\rm{(3s^2+4s+2)/(s^2(s+1))=(As+B)/(s^2)+(C)/(s+1)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/xr4vlfasr64ujtehy8npc87czztkv41tgt.png)
![\longrightarrow\rm{(3s^2+4s+2)/(s^2(s+1))=((As+B)(s+1)+Cs^2)/(s^2(s+1))}](https://img.qammunity.org/2023/formulas/mathematics/high-school/vld1zgnwptyxl1g18j6tvuzjrrgp9qkuz7.png)
![\longrightarrow\rm{3s^2+4s+2=(As+B)(s+1)+Cs^2}](https://img.qammunity.org/2023/formulas/mathematics/high-school/2wtqnz30glirsmvvap92qfb18569imfzqb.png)
![\longrightarrow\rm{3s^2+4s+2=(A+C)s^2+(A+B)s+B}](https://img.qammunity.org/2023/formulas/mathematics/high-school/7jow5r0zbmhqbx3c449uoick56o8zjhiwr.png)
Equating corresponding coefficients,
![\rm{A+C=3}](https://img.qammunity.org/2023/formulas/mathematics/high-school/sigu8hnexxcp3n6pfg8dsupi4kufnn8zz2.png)
![\rm{A+B=4}](https://img.qammunity.org/2023/formulas/mathematics/high-school/kaq252ihkrjoue2f676wtsc61k38jg0lk5.png)
![\rm{B=2}](https://img.qammunity.org/2023/formulas/mathematics/high-school/nacx2cq20ru8vj09apna8xknguw6eg0o4y.png)
Solving each equation we get,
![\rm{A=2}](https://img.qammunity.org/2023/formulas/mathematics/high-school/8n6261gk9b5qps5wnurze2jc1gum7bf1x3.png)
![\rm{B=2}](https://img.qammunity.org/2023/formulas/mathematics/high-school/nacx2cq20ru8vj09apna8xknguw6eg0o4y.png)
![\rm{C=1}](https://img.qammunity.org/2023/formulas/mathematics/high-school/aa6hxybuqooj50q5rct05ef4unmii58qni.png)
Therefore,
![\longrightarrow\rm{(3s^2+4s+2)/(s^2(s+1))=(2s+2)/(s^2)+(1)/(s+1)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/xpew4vc5rp3630kdaumf00t5d0s0qii7qs.png)
![\longrightarrow\rm{(3s^2+4s+2)/(s^2(s+1))=(2)/(s)+(2)/(s^2)+(1)/(s+1)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/iz24hccs54sx8x2kytmjgdw3j3s6kkxpjj.png)
Then (1) becomes,
![\longrightarrow\rm{X(s)=(2)/(s)+(2)/(s^2)+(1)/(s+1)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/7wawosyiaq6azy3ez8fun9z4swlkh1qdzy.png)
Now we will inverse Laplace transformation to obtain the solution.
![\longrightarrow\cal{L}^{\rm{-1}}\{\rm{X(s)}\}=\cal{L}^{\rm{-1}}\left\{\rm{(2)/(s)+(2)/(s^2)+(1)/(s+1)}\right\}](https://img.qammunity.org/2023/formulas/mathematics/high-school/jk1vnqn52gj6uf4t4578nz2vkruv4qzaoc.png)
![\small\text{$\longrightarrow\rm{x(t)}=\rm{2}\,\cal{L}^{\rm{-1}}\left\{\rm{(1)/(s)}\right\}+\rm{2}\,\cal{L}^{\rm{-1}}\left\{\rm{(1)/(s^2)}\right\}+\cal{L}^{\rm{-1}}\left\{\rm{(1)/(s+1)}\right\}$}](https://img.qammunity.org/2023/formulas/mathematics/high-school/9r3sdn7qr3ozcg4yhf9i3ki1zma58pes04.png)
![\small\text{$\longrightarrow\rm{x(t)}=\rm{2}\,\cal{L}^{\rm{-1}}\left\{\rm{(1)/(s)}\right\}+\rm{2}\,\cal{L}^{\rm{-1}}\left\{\rm{(1!)/(s^(1+1))}\right\}+\cal{L}^{\rm{-1}}\left\{\rm{(1)/(s-(-1))}\right\}$}](https://img.qammunity.org/2023/formulas/mathematics/high-school/kwvz4eaxz6qloocz8uten80jee5s9y2ops.png)
We have,
![\cal{L}^{\rm{-1}}\left\{\rm{(1)/(s)}\right\}=\rm{1}](https://img.qammunity.org/2023/formulas/mathematics/high-school/mbyewgdfblg3p1wpf3qi8nu23ynz21hkb9.png)
![\cal{L}^{\rm{-1}}\left\{\rm{(1!)/(s^(1+1))}\right\}=\rm{t}](https://img.qammunity.org/2023/formulas/mathematics/high-school/simdd90jkrrxlqqip086vn3n39vajigqk2.png)
![\cal{L}^{\rm{-1}}\left\{\rm{(1)/(s-(-1))}\right\}=\rm{e^(-t)=(1)/(e^t)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/xr9483t8tsjjwrlxs15u4725m8a60dv9wx.png)
Hence,
![\longrightarrow\rm{\underline{\underline{x(t)=2+2t+(1)/(e^t)}}}](https://img.qammunity.org/2023/formulas/mathematics/high-school/j82q4b7fswqc1ywglwdwaib0x2o9t7xi6f.png)
This is the solution to our differential equation.
![\quad](https://img.qammunity.org/2023/formulas/mathematics/high-school/sf8j0uw8zeq6itu8q0bnbfp6w2kiibev6a.png)
Some results of Laplace Transformation:-
![\boxed{\begin{array}c&\\\rm{x(t)}=\cal{L}^{\rm{-1}}\{\rm{X(s)}\}&\rm{X(s)}=\cal{L}\{\rm{x(t)}\}\\\\=============&==================\\\\\rm{(d^nx)/(dt^n)}&\rm{s^n\,X(s)}-\displaystyle\sum_{\rm{r=0}}^{\rm{n-1}}\rm{s^(n-r-1)\,(d^rx)/(dt^r)(t=0)}\\\\----------&--------------\\\\\rm{x'(t)}&\rm{s\,X(s)-x(0)}\\\\----------&--------------\\\\\rm{x''(t)}&\rm{s^2\,X(s)-s\,x(0)-x'(0)}\\\\----------&--------------\\\\\rm{a}&\rm{(a)/(s)}\\\\----------&--------------\\\\\rm{t^n,\ n}\in\mathbb{N}&\rm{(n!)/(s^(n+1))}\\\\----------&--------------\\\\\rm{e^(at)}&\rm{(1)/(s-a)}\\&\end{array}}](https://img.qammunity.org/2023/formulas/mathematics/high-school/tyq0q0bdo7w9prfjs2bf6tla9c0nko6xg8.png)